Mixed Reverse Micellar Systems (MRMS) for Extraction of Erythromycin: Effect of Surfactant Concentration on Forward Extraction Step - Siti Norazimah, Mohamad Aziz; Mimi Sakinah, A. M. (Universiti Malaysia Pahang, 2016)
Mixed reverse micellar systems (MRMS) of sodium bis(2-ethylhexyl)sulfosuccinate (AOT) and zwitterionic surfactants 3-(N,N-Dimethyloctadecylammonio) propanesulfonate (SB3-18) in iso-octane were used for the forward extraction of erythromycin from the aqueous phase to organic phase for the first time. The effect of surfactant concentration on the percentage of erythromycin transferred was investigated in detail. It was found that sufficient AOT (20 g/L) concentration was required for the solubilising of erythromycin in MRMS. Erythromycin was successfully solubilised in MRMS with higher percentage of erythromycin transfer which was 98.13% at 60.0 g/L of AOT concentration.